2002
DOI: 10.1111/j.1572-0241.2002.05953.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary trypsinogen activation peptide is more accurate than hematocrit in determining severity in patients with acute pancreatitis: a prospective study

Abstract: In comparison to admission Hct, urinary TAP was more accurate in determining severity in patients with acute pancreatitis by Atlanta, APACHE II, and Ranson criteria. We conclude that urinary TAP is a more accurate predictor of severity in patients with acute pancreatitis compared with Hct. Urinary TAP should be used to determine severity in patients early in the course of acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Although, the APACHE score can be calculated at admission and 24-hours, the accuracy of determining severity does not reach to significance until 48-hours. 9 In this study, acute necrotising pancreatitis was the most fulminant form of acute pancreatitis, i.e. 4(8.9%) cases, which is comparable with the findings of an American study conducted by Hungness ES, et al 8 However, we could not distinguish between the sterile or infected form of necrotising pancreatitis, since WBC count was raised in all forms and pus culture was not sterile.…”
Section: Gallstone Idiopathic Alcohol Traumasupporting
confidence: 88%
See 1 more Smart Citation
“…Although, the APACHE score can be calculated at admission and 24-hours, the accuracy of determining severity does not reach to significance until 48-hours. 9 In this study, acute necrotising pancreatitis was the most fulminant form of acute pancreatitis, i.e. 4(8.9%) cases, which is comparable with the findings of an American study conducted by Hungness ES, et al 8 However, we could not distinguish between the sterile or infected form of necrotising pancreatitis, since WBC count was raised in all forms and pus culture was not sterile.…”
Section: Gallstone Idiopathic Alcohol Traumasupporting
confidence: 88%
“…8 The management of patients with acute pancreatitis is complicated by the ability to distinguish mild from severe disease during the early stages. 9 In our setting, Ranson's bio-clinical criteria were used to predict the severity. This system requires 48-hours for accuracy in delivering severity.…”
Section: Gallstone Idiopathic Alcohol Traumamentioning
confidence: 99%
“…[31] Other subsequent studies revealed different sensitivity (58-100%) and specificity (65.8-77%) rates for different uTAP cut-off levels. [32][33][34] Meta-analysis determined sensitivity and specificity for uTAP >35 nmol/L of 71% and 75%, respectively (AUC=0.83). [34] Value of uTAP is that it provides useful information about severity at admission, but as it is not widely used in many hospitals, benefit is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous data from studies using markers such as necrosis on contrast-enhanced computed tomography 30,31 and TAP release. [16][17][18]32 The lack of an association between sL-selectin and outcome in acute pancreatitis is consistent with the disappointing outcome of studies of other markers of neutrophil activation, such as neutrophil elastase release. 11,[33][34][35] It seems unlikely that activation of polymorphonuclear neutrophils plays a significant part in the early pathogenesis of severe acute pancreatitis, perhaps because neutrophil activation is increased in the early phase of mild pancreatitis as much as in severe acute pancreatitis, or because any differences in neutrophil activation are masked by extensive endothelial activation.…”
Section: Pathogenesis Of Acute Pancreatitismentioning
confidence: 83%